2020
DOI: 10.1101/2020.07.24.220715
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CoVaccine HT™ adjuvant potentiates robust immune responses to recombinant SARS-CoV-2 Spike S1 immunisation

Abstract: The current COVID-19 pandemic has claimed hundreds of thousands of lives and its causative agent, SARS-CoV-2, has infected millions, globally. The highly contagious nature of this respiratory virus has spurred massive global efforts to develop vaccines at record speeds. In addition to enhanced immunogen delivery, adjuvants may greatly impact protective efficacy of a SARS-CoV-2 vaccine. To investigate adjuvant suitability, we formulated protein subunit vaccines consisting of the recombinant S1 domain of SARS-Co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…We would further like to acknowledge partial funding for these studies from R01AI132323 (National Institute of Allergy and Infectious Diseases), from P30GM114737 (Centers of Biomedical Research Excellence, National Institute of General Medical Sciences) and institutional funds. This manuscript has been released as a pre-print at BioR x iv (53).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…We would further like to acknowledge partial funding for these studies from R01AI132323 (National Institute of Allergy and Infectious Diseases), from P30GM114737 (Centers of Biomedical Research Excellence, National Institute of General Medical Sciences) and institutional funds. This manuscript has been released as a pre-print at BioR x iv (53).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Previous preclinical studies of SARS-CoV and MERS-CoV vaccines have demonstrated that the S protein plays a key role in induction of neutralizing antibody and T cell responses as well as protective immunity [16][17][18]. Stabilization of S proteins in the prefusion trimeric conformation results in increased expression, conformational homogeneity, and production of potent neutralizing antibody responses [18,27]. Current SARS-CoV-2 vaccines under development use either RBD or full-length S protein with or without modifications for stabilization of prefusion conformation as the major antigen targets.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous preclinical studies of vaccines against the highly pathogenic SARS-CoV and Middle East respiratory syndrome coronavirus (MERS-CoV) [16][17][18] as well as recent studies of patients with SARS-CoV-2 infections [19][20][21][22], S protein appears to be the antigenic target of both neutralizing antibody and T cell responses. The majority of current COVID-19 vaccines under preclinical and clinical development use full-length S proteins as antigen targets with further modifications such as removal of the polybasic sites [23][24][25], introduction of proline mutations [23,26,27], or addition of trimerization domains to preserve the native-like trimeric prefusion structure of S proteins. These antigens have been shown to mimic the native S protein presented on viral particles and preserve neutralizationsensitive epitopes [18,28].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the aluminum adjuvant that lacks the ability to mediate cellular immunity, the emulsion adjuvant can trigger a more balanced immune response by improving antigen uptake, recruiting immune cells, and promoting the activation and migration of antigen presenting cells. An experiment at the University of Hawaii in the United States evaluated the immune effect of Covaccine HT adjuvant compounded with S1 subunit of spike protein of novel coronavirus [6]. The experimental results showed that after immunizing mice for a single time (day 14), serum antibody analysis showed that the specific IgG antibody titer of Covac group was significantly higher than that of aluminum adjuvant group (the titer level of aluminum adjuvant group was close to the baseline), and the results of microsphere immunoassay data also confirmed that immunization with S1 subunit of COVID-19 and Covaccine HT adjuvant could induce a high level of antigen-specific IgG response.…”
Section: Emulsion Adjuvantmentioning
confidence: 99%